A Systematic Literature Review of the Barriers to Job Placement for Person with Disabilities - Farah Anuaruddin, Nurfarhani; Husna Abdull Rahman, Rabeatul; Abdul Patah, Salwa; Ayue Abd Rahman, Azra (International Journal of Engineering and Technology, 2018)
People often fail to realize that the disabled population is an important but largely untapped human resource. Prejudices and misconceptions about person with disabilitiesâ€™ ability to perform and compete in the open market are likely to be the cause. This research endeavor provides an overview of some of the factors that contributes for low ratio of job placements for persons with disabilities. Study about such factors is imperative so as to improve understanding regarding this phenomenon and increase employment opportunities for person with disabilities. Review of literature is carried out to highlight the barriers to job placement for persons with disabilities. Some of the barriers highlighted in this study are the attitude of the employers towards the hiring of persons with disabilities, job demand, and attitude of disabled persons. This paper concludes that more training and awareness programs should be conducted to educate employers about human resource policies, practices and strategies for persons with disabilities to improve their participation in the mainstream workforce. This research will have useful implications for the policy makers for incorporating untapped human resource in the form of persons with disabilities.Â Â